The Ability to Pay and Willingness to Pay on Operation of Adi Soemarmo Airport Train Access Line to Airplane Passengers - Wahyu Chrismasto; Imam Muthohar; Danang Parikesit (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
Connectivity between transportation nodes is crucial in encouraging the movement of people and goods, including access to Adi Soemarmo Airport. Currently, access to Adi Soemarmo Airport is dominated by private vehicles and taxis compared to public transportation such as buses which can be costly for some passengers. To cut the cost of transportation in Adi Soemarmo airport, the Ministry of Transportation has built railway access to Adi Soemarmo Airport from Solo Balapan Station and vice versa. However, the scheme of train’s tariff is solely designed to accommodate only operational and maintenance cost, while the ability and willingness of passengers to pay are simply neglected. This research aims to analyse willingness to pay of airplane passenger for the operation plan of airport train based on mode choice model and contingent valuation method and finally be able to determine the tariff based on willingness to pay and train operating costs. Mode choice model uses logit binomial in terms of differences with a stated preference method, willingness to pay analysis uses the net economic value from binomial logit and train operating cost calculations use the Minister of Transportation Regulation Number PM 17 the Year 2018. The average value of willingness to pay of prospective airport train users for each car, taxi and bus users based on binomial logit model is IDR14,802.42, IDR14,121.13, IDR14,221.42. Meanwhile, the value of the ability to pay for each car, taxi and bus users is IDR60,996.90, IDR79,564.67, IDR55,117.17 and the tariff value based on train operating costs is IDR17,730.22.